The Development of Malang City Virtual Tourism for Preservation of Traditional Culture using React 360 - Tolle, Herman; Kurnia S., Primananda; Sukmo Wardhono, Wibisono; Dewi, Ratih Kartika; Fanani, Lutfi; Afirianto, Tri (MATICS: Jurnal Ilmu Komputer dan Teknologi Informasi (Journal of Computer Science and Information Technology), 2023)
Malang is one of the tourist destinations in East Java, and always visited by both domestic and foreign tourists. However, Malang isn’t the first destination in tourism, this is due to the lack of intense promotion. Virtual tourism is a virtual reality technology for promoting tourism. Based on these problems, the researchers developed a virtual reality application that can provide immersive experiences to users assembled with tourist destinations in Malang. Application was developed using React 360 framework, because of its ease of development and can be developed for various platforms. The Software Development Life Cycle (SDLC) is the waterfall method. The implementation using VR Headset and VR Controller. In testing, researchers conducted functional testing and non-functional testing. Functional testing is done using black box testing and non-functional testing is done by the System Usability Scale (SUS) method. The results of functional testing using black box are 100% valid. In the usability test, the System Usability Scale (SUS) questionaire obtained a score of 89. From the scores that have been obtained, this application is acceptable, with Grade A and adjective rating Excellent.